1996
DOI: 10.1182/blood.v87.2.423.bloodjournal872423
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia and lymphoma in ataxia telangiectasia

Abstract: There is a large increase in lymphoid malignancy in A-T patients and a total absence of myeloid tumors. Penetrance of the tumor phenotype is about 10% to 15% by early adulthood. The increase in lymphoid malignancy includes both B- and T-cell tumors. However, young A-T patients do not show an increased susceptibility to cALL, and the UK data suggest that B-cell lymphoma occurs in older A-T children. T-cell tumors may occur at any age and may be T-ALL, T-cell lymphoma, or T-PLL; most strikingly, there may be a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
156
0
6

Year Published

1998
1998
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 550 publications
(168 citation statements)
references
References 49 publications
2
156
0
6
Order By: Relevance
“…2,3) A large proportion of patients with T-cell prolymphocytic leukemia (T-PLL) and T-cell leukemia developing from ataxia telangiectasia carry t(14;14)(q11;q32), inv(14)(q11;q32) or t(7;14)(q35;q32), which juxtapose the TCL1 locus to the α/δ or β loci of the T cell receptor (TCR). [4][5][6] This points to the presence of a gene which is activated by the juxtaposition of TCR, as found for MYC or BCL2 translocations with activation by the immunoglobulin gene (Ig) in B-cell malignancies. Virgilio et al 7) recently identified a transcript from the TCL1 locus and designated it as the TCL1 gene, although direct evidence for activation by juxtaposition to TCR genes remains elusive.…”
mentioning
confidence: 86%
“…2,3) A large proportion of patients with T-cell prolymphocytic leukemia (T-PLL) and T-cell leukemia developing from ataxia telangiectasia carry t(14;14)(q11;q32), inv(14)(q11;q32) or t(7;14)(q35;q32), which juxtapose the TCL1 locus to the α/δ or β loci of the T cell receptor (TCR). [4][5][6] This points to the presence of a gene which is activated by the juxtaposition of TCR, as found for MYC or BCL2 translocations with activation by the immunoglobulin gene (Ig) in B-cell malignancies. Virgilio et al 7) recently identified a transcript from the TCL1 locus and designated it as the TCL1 gene, although direct evidence for activation by juxtaposition to TCR genes remains elusive.…”
mentioning
confidence: 86%
“…A gene upstream of TP53 that has been implicated in the predisposition to lymphoid malignancies such as T-prolymphocytic leukaemia (T-PLL) and CLL is the ATM gene, a protein kinase mutated in the genetic instability syndrome called ataxia-telangiectasia (Taylor et al, 1996). Its major function is to maintain genetic stability by activating G1/S, S and G2/M cell cycle checkpoints in response to DNA double-stranded break damage (Shiloh, 2003).…”
Section: Deregulation Of Tp53 By Genes In the Tp53 Pathwaymentioning
confidence: 99%
“…Thirdly, myeloma is characteristically associated with chromosome translocations involving the IgH locus at 14q32. Translocations involving breakpoints in immune system genes are seen at a much higher rate in lymphocytes of A-T patients, defective in ATM, compared with normal and indeed, progenitors carrying such translocations have been shown to give rise to T-cell prolymphocytic leukaemia in these patients (Taylor et al, 1996). Interestingly, the ATM R3047X mutation was observed in a patient with T-cell prolymphocytic leukaemia and concomitant IgA myeloma, carrying a t(14;14)(q11;q32) translocation (Zech et al, 1983;Vorechovsky et al, 1997).…”
mentioning
confidence: 99%